An updated checklist of the birds of Rio Grande do Norte, Brazil, with comments on new, rare, and unconfirmed species - Sagot-Martin, François; Lima, Rafael Dantas; Pacheco, José Fernando; Irusta, Jorge Bañuelos; Pichorim, Mauro; Hassett, David Maurice (Bulletin of the British Ornithologists' Club, 2020)
We present a detailed bird list for the north-east Brazilian state of Rio Grande do Norte. This is the first inventory of the avifauna of the state that complies with strict criteria as to its compilation and documentation. To achieve this, we reviewed all records published for the state, as well as records in several online databases and museum collections. Our consolidated list is enhanced by our own unpublished records, and encompasses 425 species, 391 of them based on available specified physical evidence. The list includes 12 taxa not previously documented in the state and 35 documented taxa that are considered nationally or globally threatened. Other noteworthy records include three documented range extensions of 1,000 km or more and the first proven breeding by three species in far north-eastern Brazil. The rather diverse avifauna of Rio Grande do Norte reflects its location at the juxtaposition of three major domains: Atlantic Forest, Caatinga, Cerrado, and their ecotones, bordered by a marine environment.